The effectiveness of early mobilization to improve flexibility after arthroplasty knee: a meta-analysis - Arif Pristianto; Dwi Tiara Anjani; Ibaadurrohmaan; Avida Kurniasari; Putri Isha Fidhia Arofah; Syailendra Wijaya (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Knee arthroplasty is a surgical procedure in the knee area to replace the joint with a fixed-bearing implant, after knee arthroplasty functional abilities will decrease. One intervention that can be carried out to improve the function after knee arthroplasty is by providing early mobilization. The purpose of this study was to evaluate how well early mobilization improves knee arthroplasty patients' range of motion. Methods: This meta-analysis was conducted with a sample size of 9 research studies with a total of 511 subjects. The search for articles was carried out using the PICO criteria consisting of population, namely patients with knee arthroplasty conditions, the intervention provided is early mobilization, comparison with standard care, and outcomes improve flexibility and functional ability. Results: Meta-analysis of 9 randomized controlled trial studies showed that EM significantly improved the flexibility of TKA patients (SMD=0.56; 95% CI=0.15-0.97, p=0.007), although with high heterogeneity (I2=79%) and indications of publication bias. Conclusion: EM is effective in improving the flexibility of patients after knee surgery. Conclusion: Early mobilization can increase flexibility compared to patients who are only given standard care.